Construction of an evaluation indicator system for the integrated development of sports, culture and tourism based on tourist perceptions - Yudong Tang; Jianying Li; Cheng Xing (Scientific Reports)
Abstract Through a literature review, expert interviews, questionnaires, and statistical methods, this study constructs an evaluation index system and calculates the score for the integrated development of sports, culture, and tourism at sports event venues, specifically the Hemei Rural Football Super League (“Village Super League”) in Rongjiang, Guizhou. First, we reviewed and analyzed the relevant literature, which led to the formation of an initial index consisting of 18 items. The index was optimized after the analysis to include three main dimensions and 13 specific measurement items. The refined index demonstrated good reliability and validity and may thus provide a valuable tool for evaluating the sustainable development of sports, culture, and tourism integration in specific regions.